Perlindungan Konsumen Pemilik Barang Atas Kerugian yang Dialami Akibat Terbakarnya Gudang Ekspedisi JNE Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Nailla Rahma; Sudaryat Sudaryat; Deviana Yuanitasari (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The case of the burning of the JNE Cimanggis storage branch warehouse, Depok is the focus of this research. After the fire incident, JNE issued a statement of commitment to carry out a compensation process for affected customer goods, which also included damage to property in the surrounding community. This research identifies that consumers who experience losses have the option to file a lawsuit, either through litigation or non-litigation. The litigation process involves filing a lawsuit in civil court, while non-litigation includes an out-of-court approach with the aim of reaching a mutually beneficial agreement. Legal norms in consumer protection function as a legal framework for assessing violations of consumer rights. Although it is hoped to provide a solution, in practice, there are gaps and confusion regarding the implementation of the law, especially when the courts are involved in examining cases that challenge the decisions of the Consumer Dispute Resolution Agency (BPSK), due to aspects of the Civil Procedure Law. Apart from completing non-litigation settlements, consumers can also file a Class Action lawsuit with the court. Class Action is a legal development in Indonesia that allows people to submit or defend their rights collectively through representatives. The results of this research reflect the complexity in guaranteeing the rights of consumers who own goods who suffered losses due to the fire in the shipping warehouse, by emphasizing resistance in the implementation of consumer protection laws and the importance of alternative solutions, including Class Action lawsuits.